THE PROBLEM OF POST-OPERATIVE NAUSEA AND VOMITING IN THE PATIENTS UNDERGOING NEUROSURGERY - M. I. Klyukin; A. S. Kulikov; A. Yu. Lubnin (Вестник анестезиологии и реаниматологии, 2018)
The review presents the most recent data on the causes, frequency, risk factors, prevention methods, and principles of management of post-operative nausea and vomiting. The special attention is paid to specific aspects of this type of adverse reactions to anesthesia in the neurosurgical practice. The review concludes that it is still necessary to search for better methods of prevention and management of post-operative nausea and vomiting in the group of neurosurgical patients considering the specific risk factors.